Matter : poems - Ramke, Bin, 1947- (Kuhl House poets., 2004)
Bin Ramke's poetry has always been concerned with separating the real from the wished-for or the feared. In Matter, Ramke investigates not only the physical realities of our world but the qualities that make things important to us, that give them weight. These poems, often in the voice of a child, are full of yearning and anguish but also an appreciation for the enhanced perceptions and small pleasures to be found among the sadness. "All lost things have the same voice," he says, and this universal voice reminds us of home and family and the simple connections of ordinary lif